What is Good Academic Writing? Insights into Discipline-Specific Student Writing - Whong, Melinda; Godfrey, Jeanne (New Perspectives for English for Academic Purposes, 2020)
This book is published open access. The field of English for Academic Purposes (EAP) developed to address the needs of students whose mother tongue is not English. However, the linguistic competence required to achieve academic success at any university where English is the medium of instruction is a challenge for all students. While there are linguistic features common to academic literacy as a general genre, closer investigation reveals significant differences from one academic field to another. This volume asks what good writing is within specific disciplines, focussing on student work. Each chapter provides key insights by EAP professionals, based on their research in which they bring together analysis of student writing and interviews with subject specialists and markers who determine what 'good writing' is in their discipline. The volume includes chapters on established disciplines which have had less attention in the EAP and academic writing literature to date, including music, formal linguistics, and dentistry, as well as new and growing fields of study such as new media. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Knowledge Unlatched.